Keragaman dan Kelimpahan Plankton Sebagai Bioindikator Kualitas Lingkungan di Perairan Pantai Jayapura - Dewi Sulistiowati; Rosye H.R. Tanjung; Daniel Lantang (Jurusan Biologi FMIPA Universitas Cenderawasih, 2016)
The aims of this research were to know the water environmental quality and to determine the diversity and abundance of plankton in Youtefa and Yos Sudarso Bay. The Sampling was conducted from October 2012 to January 2013 at two observation stations of Youtefa Bay and four observation stations of Yos Sudarso Bay during the dry and rainy seasons. The Sampling of plankton in each observation stations were made horizontally using a plankton net size number of 25. Biological data are determined using diversity index, uniformity index, dominance index and abundance calculations. Physico-chemical parameters were analyzed descriptively by comparing the result data of research with waters quality standards for marine’s biota based on decree of Environment Minister No. 51 year 2004. The results of water quality showed that in general, the quality of aquatic environment in Youtefa and Yos Sudarso Bay did not comply with water quality standards for marine’s biota issued by The Minister of Environment of Republic of Indonesia. While based on the diversity index analysis, water quality in Youtefa and Yos Sudarso Bay was categorized as a half polluted-heavily polluted. Diversity of plankton in Youtefa and Yos Sudarso Bay during the dry and rainy seasons was categorized as low-medium. Abundance of plankton in Youtefa and Yos Sudarso Bay was in low category. Key words: Abundance, diversity, plankton, Youtefa Bay, Yos Sudarso Bay.